2020
DOI: 10.1111/jdi.13256
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of mild cognitive impairment in type 2 diabetes mellitus is associated with serum galectin‐3 level

Abstract: Aims/Introduction Galectin‐3 (Gal3) contributes to insulin resistance, inflammation and obesity, the three risk factors for mild cognitive impairment (MCI) in type 2 diabetes mellitus patients. Materials and methods A total of 134 hospitalized type 2 diabetes mellitus patients were assessed by the Montreal Cognitive Assessment method, and divided into 65 MCI and 69 controls. Levels of variables, Gal3 and Aβ42, were investigated in relation with cognitive function in both type 2 diabetes mellitus patients with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 42 publications
1
12
0
Order By: Relevance
“…Hyperglycemia is a well-recognized risk factor of cognition decline. Uncontrolled HbA1c levels were detected in our previous studies [ 34 36 ] and other works [ 37 ]. Although HbA1c levels were not significantly different, higher HbA1c levels were measured in patients with MCI than in patients without MCI in the present study.…”
Section: Discussionmentioning
confidence: 61%
“…Hyperglycemia is a well-recognized risk factor of cognition decline. Uncontrolled HbA1c levels were detected in our previous studies [ 34 36 ] and other works [ 37 ]. Although HbA1c levels were not significantly different, higher HbA1c levels were measured in patients with MCI than in patients without MCI in the present study.…”
Section: Discussionmentioning
confidence: 61%
“…Recently, research has focused on cerebrovascular and neurodegenerative chronic complications of diabetes, such as diabetes-associated cognitive impairment [ 109 ]. In our previous study, we found that serum Gal-3 was significantly higher in T2DM patients with mild cognitive impairment (MCI) than in T2DM controls, even after adjustment for multiple potential confounders [ 110 ]. Similarly, Gal-3 levels in the serum and brain were increased in diabetic rats and were associated with neuroinflammation, oxidative stress, learning and memory impairment, while administration of MCP could reverse these outcomes [ 105 ].…”
Section: Main Textmentioning
confidence: 99%
“…In agreement with other reports, the authors also showed that GCS-100, an antagonist of Gal-3, induced cancer cell death [ 190 , 191 , 192 ], boosted tumor-infiltrating T lymphocyte secretion of IFN-gamma [ 143 ], and increased prostate cancer sensitivity to cisplatin [ 193 ]. Similarly, an effect was observed in response to modified citrus pectin (MCP) on cancer [ 67 , 95 , 194 , 195 ]; however, MCP can also be used for other Gal-related disease treatments, such as decreasing Gal-3 levels in type 2 diabetes [ 196 ], decreasing doxorubicin-induced cardiovascular diseases [ 197 ], ameliorating cardiac dysfunction [ 198 ], and improving ischemic heart failure [ 199 ]. In addition, the calixarene derivative compound “OTX-008” was designed as a Gal-1 inhibitor [ 200 ].…”
Section: Available Inhibitors For Targeting Galectinsmentioning
confidence: 99%